NATIONAL AND INTERNATIONAL COOPERATION IN THE PREVENTION AND ERADICATION OF MONEY LAUNDERING - Husein, Yunus (UI Scholars Hub, 2021)
The Prevention and eradication of money laundering, as part of the new paradigm in the effort to combat crimes, has its own mechanism in both national and international cooperation, particularly in relation to information exchange. The cooperation is pursuant to a Memorandum of Understanding, but can also be simply pursuant to the principle of reciprocity among parties. Once effective, this cooperation will strengthen the performance of Indonesian Financial Transaction Report and Analysis Center (INTRAC/PPATK) in performing its duties and exercising its authority as the Financial Intelligence Unit.